An Investigation Over Rock Wettability And Its Alteration On Some Indonesian Sandstones - Bambang Widarsono (Scientific Contributions Oil and Gas, 2010)
Wettability is a reservoir rock property that is not easy to measure and quantify but has a crucial effect on other rock properties such as relative permeability, capillary pressure, and electrical properties. Problem that may occur with regard to this matter is that those properties are often measured on already cleansed core samples as part of the standard procedure. Having undergone the normally utilized heated cleansing process alteration in the rock’s original wettability was often reported. Under such condition, unrepresentative wettability certainly leads to unrepresentative measured data with all of consequences. This article presents a study that uses 363 sandstone samples retrieved from 28 oil and gas fields in Indonesia. The study consists of two stages of analysis. First analysis is performed on data obtained from three wettability tests results while the second one is made with using water-oil relative permeability data, that is usually measured on cleansed core samples. Original wettability data shows that the sandstones varry in wettability from water-wet to oil-wet (48.2% and 30.2% of total samples, respectively). Comparison between data of the two analyses shows that original wettability tends to degrade in strength after cleaning down to neutral wettability, among which neutral wettability appears to be the largest in number (49.1% of total sample). Results also show that weak wettability tends to endure more than stronger ones. The overall results have demonstrated the need for caution in core handling and for measures that can minimize the risk.